Bridging the Divine: The Construction of Sufism Thought by Akang Arfan Abdullah Syafi'i - Hamid, Asep Lukman; Sa'ari, Che Zarrina; Yuda, Dendi; Feriyanto, Feriyanto (UIN Sunan Gunung Djati Bandung, 2023)
This study examines the influence of Akang Arfan Abdullah Syafi'i's interpretation of Sufism within the Judatul Uqba Pesantren in Sukabumi, West Java. The research focuses on how Syafi'i's Sufism has resonated with and attracted a significant following among the local community, encouraging them to engage deeply with Sufi practices in their daily lives. This phenomenon is evidenced by the extensive participation in Sufi recitations and the growth of the Yā Wakῑl congregation across Indonesia. Employing a qualitative descriptive methodology, the study gathers data through observation, interviews, and documentary analysis. Central to Syafi'i's teaching is the concept of 'wushūl'—a spiritual connection to Allah SWT, facilitated through 'dzikr' (remembrance of Allah) and acts of charity. These practices are seen as dual pathways: 'dzikr' connects an individual to Allah (habl min Allah), while charity fosters interpersonal bonds (habl min an-Nās). The balance between these spiritual and social dimensions is posited as crucial for the cultivation of Islamic virtues and the attainment of the 'insān kāmil' or the perfect human being.